From Politics to the Mataraman Cultural Stage: Fragments of Magetan History in the XVII-XX Centuries - Subaryana Subaryana; Indra Fibiona; Wahyu Pambudi; Nugraha Nugraha (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
The historical trajectory of East Java, particularly Magetan, is intricately linked with the broader political and cultural developments of Central Java and Yogyakarta, especially since the Hindu-Buddhist era and the subsequent rise of Mataram Islam. This research investigates how historical political dynamics have shaped contemporary cultural identities in the Magetan region. Through a historical approach and the analysis of various archival sources, the study examines key political events, including the conquest of Kanitèn, the Trunojoyo rebellion, and the Chinese Insurrection, and their impacts on Magetan. The findings reveal that the political maneuvers of Mataram Islam, coupled with Dutch colonial intervention, significantly influenced the cultural landscape in Magetan. The concept of keagungbinataraan mandated Magetan’s allegiance to the Yogyakarta Sultanate, resulting in the adoption of Mataraman culture as an expression of loyalty. The political rivalry between the Surakarta and Yogyakarta palaces intensified cultural contestations, with Magetan predominantly aligning with the Yogyakarta Sultanate, as evidenced by the prevalent use of the slendro-tuned gamelan. These results underscore the enduring influence of historical political events on Magetan’s cultural identity, which continues to evolve in the present day.